2007
DOI: 10.1124/jpet.107.132308
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor-Independent Neuroprotection via Protein Phosphatase Preservation and Attenuation of Persistent Extracellular Signal-Regulated Kinase 1/2 Activation

Abstract: The mechanism of estrogen-mediated neuroprotection is not yet clear. Estrogens have a variety of modes of action, including transducing signaling events such as activation and/or suppression of the mitogen-activated protein kinase (MAPK) pathway. We have previously shown protein phosphatases to be involved in 17␤-estradiol-mediated neuroprotection. In the present study, we assessed the role of estrogen receptors (ERs) in estrogen-mediated neuroprotection from oxidative/excitotoxic stress and the consequential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 43 publications
4
45
1
Order By: Relevance
“…Changes in the activity of these enzymes can regulate the phosphorylation of numerous cellular substrates such as intermediary signaling proteins Rsk, p38, JNK, and the nuclear transcriptional factors CREB and cfos/c-Jun, which may ultimately mediate cell survival changes (for a review, see [55]). However, ERK1/2 is rapidly and persistently phosphorylated in response to oxidative and excitotoxic stresses caused by glutamate and the presence of estrogens prevents this persistent phosphorylation (Figure 2.4); [56]. These data suggest that prolonged phosphorylation of ERK1/2 is detrimental to cell survival; this is supported by the observations by Smith and colleagues who noted aberrant neuronal expression of phosphorylated ERK1/2 and other MAPKs in AD brains in association with markers of oxidative stress [57].…”
Section: In Vitro Assessment Of Structure-cell Signaling Relationshipssupporting
confidence: 79%
See 2 more Smart Citations
“…Changes in the activity of these enzymes can regulate the phosphorylation of numerous cellular substrates such as intermediary signaling proteins Rsk, p38, JNK, and the nuclear transcriptional factors CREB and cfos/c-Jun, which may ultimately mediate cell survival changes (for a review, see [55]). However, ERK1/2 is rapidly and persistently phosphorylated in response to oxidative and excitotoxic stresses caused by glutamate and the presence of estrogens prevents this persistent phosphorylation (Figure 2.4); [56]. These data suggest that prolonged phosphorylation of ERK1/2 is detrimental to cell survival; this is supported by the observations by Smith and colleagues who noted aberrant neuronal expression of phosphorylated ERK1/2 and other MAPKs in AD brains in association with markers of oxidative stress [57].…”
Section: In Vitro Assessment Of Structure-cell Signaling Relationshipssupporting
confidence: 79%
“…Indeed, it has been shown that estrogens alone cause a rapid but transient increase in ERK1/2 phosphorylation [52,61]. In addition, it has also demonstrated that estrogens attenuate the persistent ERK1/2 phosphorylation caused by cytotoxic insults [56][57][58][59][60]. Glutamate-induced toxicity causes an increase in phosphorylation of ERK1/2 ([56]; Figure 2.4).…”
Section: In Vitro Assessment Of Structure-cell Signaling Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other ent-steroids have been synthesized (58) and evaluated as probes of natural steroid interactions including ent-cholesterol (59,60), ent-progesterone (61), ent-estrogen (62), and enantiomeric neuroactive steroids (63,64). These reports illustrate that natural and enantiomeric steroids have distinctly different interactions with chiral environments, such as receptor-binding pockets.…”
Section: Discussionmentioning
confidence: 99%
“…17 Estrogen can also provide neuroprotection through an ER-independent pathway. 20,21 However, the exact neuroprotective mechanism of E 2 under neuronal iron overload is still unclear. Surprisingly, the results from our present study showed that Trx induction by FC in the CN was significantly greater in male than female rats.…”
Section: Discussionmentioning
confidence: 99%